Excellent piezoelectric properties of PNN‐PHT ceramics sintered at low temperature with CuO addition. Issue 2 (14th August 2019) - Xia, Yushun; Li, Zhimin; Yan, Yangxi; Zhao, Mo; Zhang, Maolin; Zhang, Dongyan
Abstract: Multilayer components with excellent piezoelectric performance have been developed for fulfilling the requirement of new‐generation electromechanical devices and systems. Multilayering of the piezoelectric ceramic requires good sinterability preferentially at lower temperature. In this study, copper (II) oxide (CuO) was utilized as the sintering additive to increase the sinterability of 0.49Pb(Ni1/3 Nb2/3 )O3 –0.51Pb(Hf0.3 Ti0.7 )O3 (PNN‐PHT) ceramics at low temperature, and simultaneously enhance the piezoelectric and dielectric properties of the ceramics. The results demonstrated that the addition of CuO influenced the sintering behavior, grain growth, and piezoelectric properties of the PNN‐PHT ceramics. A ternary high performance piezoelectric PNN‐PHT ceramic sintered at 1050°C with 0.5 mol% CuO exhibited excellent properties as follows: d 33 = 912 pC N −1 and ε r = 6665.